Building a more globalized order (2020)
While the pandemic facilitated nationalist backlash against global supply chains and international organizations, it has actually revealed we need more globalization, not less. Our problem is overreliance on single-sourcing supplies rather than on a multiplicity of suppliers. Another issue is overreliance on a single international health organization malleable by the country in possession of its presidency rather than a web of many formal and informal groupings whose interests compete to produce Madisonian checks on power and provide a maximum of information as a basis for national and international action. Our vision for a better world should be an international order of greater connectedness and greater accountability. The method and means for attaining such an order should be to use the tools of free societies to protect and advance free societies